PENGARUH DANA PERIMBANGAN DAN BELANJA DAERAH TERHADAP KINERJA KEUANGAN DENGAN PENDAPATAN ASLI DAERAH SEBAGAI VARIABEL MODERASI - Tungki Ariwibowo (Universitas Slamet Riyadi, 2015)
The purpose of this research is to analyze the effect of equalization funds and shopping areas against financial performance with the original area as variable income moderation at the district/city of Central Java province in the period 2010 – 2013. This study uses census study approach. The population in this research is the whole district/city of Central Java province by as much as 35 district/municipality which consists of 29 Counties and six cities. The number of samples in this study is the whole district/city of Central Java province in as many as 35 district/city. Engineering data collection using the documentation. Data analysis techniques using a classic assumption test, multiple linear regression analysis, t-test, F-test, the coefficient of determination and the absolute difference test. The results showed that Equalization Fund and shopping areas and significant negative effect on performance of regional financial (ratio of independence) on the district/city of Central Java province in the period 2010 – 2013. The original regional income positive and significant effect on performance of regional financial (ratio of independence) on the district/city of Central Java province in the period 2010 – 2013. The original area of influence to moderate income fund balances and expenditures against regional financial performance at the district/city of Central Java province in the period 2010 – 2013, proved to be the truth. Keywords: Equalization Funds, shopping districts, and the ratio of the area of the original Income Independence